(3TQM efXheI KdGKjGJ GdoHNGQis - (3CHh YHO Gddg eMeO GHf ESeGYjd GdLYaj GdMGaXs; (3CHh YHO Gddg eMeO Hf ESeGYjd Hf EHQGgje GdLYaj GdHNGQj, GdEeGe GdHNGQj,J (B256 (3g` s
(3ChdgG (B:s
(3hHYO adeG cGf CUM cJH MOjK GdfHj Udi Gddg Ydjg hSde Ydi GdEWdGb cJGH GdHNGQj hcGf CYdi eGajg ef GdCSGfjO eG cGf KdGKjkG s
(3BNQgG (B:s
(3hSHb aj GdESfGO GdKGdK Cfg MOjK hGMO aj KdGKI ehGV ajSbW HgPG GdEYJHGQ ef GdYOI aj GdKdGKjGJ hGdMeO ddg QH GdYGdejf hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg hSde s
(3GdfSNI HgG MhGTs
(3fSNI KGfjIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B34 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B52s
Keywords: (3GdMOjK h GdeUWdMs